Cana of Galilee - Alexandre, Yardenna. (Jerusalem)
ix, 471 sayfa
Keywords: “This volume describes the results of multiple small-scale salvage excavations that took place at the site of Karm er-Ras in the Lower Galilee between 1999 and 2011. Archaeological remains of ten strata were revealed, dating from Iron Age II to the Byzantine period, including architecture, pottery, glass, coins and special finds. The archaeological data reveals the history of settlement of this site, and its changing ethnic and religious affinities over some 1500 years. Following detailed analysis of the archaeological data and the literary sources, the author argues for the identification of the Roman-period village at Karm er-Ras with ‘Cana of Galilee’, mentioned in the New Testament as the site where Jesus performed the miracle of changing water into wine“ --